Evaluasi Kualitas Website J-KREP (Jember Kesbangpol Rekomendasi Penelitian) Menggunakan Metode E-Govqual dan Importance Performance Analysis (IPA) - Achmad Azka Muaffan Sutomo Putra (Fakultas Ilmu Komputer, 2024)
J-KREP (Jember Kesbangpol Rekomendasi Penelitian) is a web-based application that is an innovation by the Government of Jember Regency through BAKESBANGPOL (Badan Kesatuan Bangsa dan Politik). This service is designed to facilitate researchers or academics in obtaining research recommendation letters. This study uses the E-Govqual method to determine the quality of the J-KREP service as perceived by users, as well as the IPA method to help prioritize indicators that require improvement. The analysis results will show the quality of service provided and which indicators need improvement recommendations. This research uses four variables from E-Govqual with 21 statement indicators that have been discussed with the service provider. The research results indicate that the average performance rating across all E-Govqual variables is 3.42. The average importance score across all E-Govqual variables is 3.65. From this, a gap value between performance and importance of -0.23 was obtained, indicating that the performance of the J-KREP service has not met users' expectations or needs. The conformity analysis between performance and importance yields a conformity value of 93.81%, meaning that the service performance is still less aligned with users' expectations or needs. There are 7 indicators in Quadrant 1, which means they are a top priority for improvement. These seven indicators include: Information displayed on this E-Government site is always updated (EF6), The acquisition of username and password on this E Government site is adequate (TR1), Only the required personal data is provided for authentication on this E-Government site (TR2), The data provided by users on this E-Government site is securely archived (TR3), Employees show genuine interest in solving users' problems (CS1), Employees have the knowledge to answer users' questions (CS3), and Employees have the ability to deliver services with confidence and assurance (CS4).
Dosen Pembimbing Utama : Fajrin Nurman Arifin, S.T., M.Eng Dosen Pembimbing Anggota : Karina Nine Amalia, S.Kom., M.Kom
Keywords: E-Government; E-Govqual; IPA